(x-4+5i)(x-4-5i)=0

Simple and best practice solution for (x-4+5i)(x-4-5i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4+5i)(x-4-5i)=0 equation:


Simplifying
(x + -4 + 5i)(x + -4 + -5i) = 0

Reorder the terms:
(-4 + 5i + x)(x + -4 + -5i) = 0

Reorder the terms:
(-4 + 5i + x)(-4 + -5i + x) = 0

Multiply (-4 + 5i + x) * (-4 + -5i + x)
(-4(-4 + -5i + x) + 5i * (-4 + -5i + x) + x(-4 + -5i + x)) = 0
((-4 * -4 + -5i * -4 + x * -4) + 5i * (-4 + -5i + x) + x(-4 + -5i + x)) = 0
((16 + 20i + -4x) + 5i * (-4 + -5i + x) + x(-4 + -5i + x)) = 0
(16 + 20i + -4x + (-4 * 5i + -5i * 5i + x * 5i) + x(-4 + -5i + x)) = 0

Reorder the terms:
(16 + 20i + -4x + (-20i + 5ix + -25i2) + x(-4 + -5i + x)) = 0
(16 + 20i + -4x + (-20i + 5ix + -25i2) + x(-4 + -5i + x)) = 0
(16 + 20i + -4x + -20i + 5ix + -25i2 + (-4 * x + -5i * x + x * x)) = 0

Reorder the terms:
(16 + 20i + -4x + -20i + 5ix + -25i2 + (-5ix + -4x + x2)) = 0
(16 + 20i + -4x + -20i + 5ix + -25i2 + (-5ix + -4x + x2)) = 0

Reorder the terms:
(16 + 20i + -20i + 5ix + -5ix + -25i2 + -4x + -4x + x2) = 0

Combine like terms: 20i + -20i = 0
(16 + 0 + 5ix + -5ix + -25i2 + -4x + -4x + x2) = 0
(16 + 5ix + -5ix + -25i2 + -4x + -4x + x2) = 0

Combine like terms: 5ix + -5ix = 0
(16 + 0 + -25i2 + -4x + -4x + x2) = 0
(16 + -25i2 + -4x + -4x + x2) = 0

Combine like terms: -4x + -4x = -8x
(16 + -25i2 + -8x + x2) = 0

Solving
16 + -25i2 + -8x + x2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -25i2 + -8x + -16 + x2 = 0 + -16

Reorder the terms:
16 + -16 + -25i2 + -8x + x2 = 0 + -16

Combine like terms: 16 + -16 = 0
0 + -25i2 + -8x + x2 = 0 + -16
-25i2 + -8x + x2 = 0 + -16

Combine like terms: 0 + -16 = -16
-25i2 + -8x + x2 = -16

Add '8x' to each side of the equation.
-25i2 + -8x + 8x + x2 = -16 + 8x

Combine like terms: -8x + 8x = 0
-25i2 + 0 + x2 = -16 + 8x
-25i2 + x2 = -16 + 8x

Add '-1x2' to each side of the equation.
-25i2 + x2 + -1x2 = -16 + 8x + -1x2

Combine like terms: x2 + -1x2 = 0
-25i2 + 0 = -16 + 8x + -1x2
-25i2 = -16 + 8x + -1x2

Divide each side by '-25'.
i2 = 0.64 + -0.32x + 0.04x2

Simplifying
i2 = 0.64 + -0.32x + 0.04x2

Reorder the terms:
-0.64 + i2 + 0.32x + -0.04x2 = 0.64 + -0.32x + 0.04x2 + -0.64 + 0.32x + -0.04x2

Reorder the terms:
-0.64 + i2 + 0.32x + -0.04x2 = 0.64 + -0.64 + -0.32x + 0.32x + 0.04x2 + -0.04x2

Combine like terms: 0.64 + -0.64 = 0.00
-0.64 + i2 + 0.32x + -0.04x2 = 0.00 + -0.32x + 0.32x + 0.04x2 + -0.04x2
-0.64 + i2 + 0.32x + -0.04x2 = -0.32x + 0.32x + 0.04x2 + -0.04x2

Combine like terms: -0.32x + 0.32x = 0.00
-0.64 + i2 + 0.32x + -0.04x2 = 0.00 + 0.04x2 + -0.04x2
-0.64 + i2 + 0.32x + -0.04x2 = 0.04x2 + -0.04x2

Combine like terms: 0.04x2 + -0.04x2 = 0.00
-0.64 + i2 + 0.32x + -0.04x2 = 0.00

The solution to this equation could not be determined.

See similar equations:

| -7a+3a=-12 | | 5t+3t=-16 | | 4-2^2-6^2/6 | | -4+6x=3x+11 | | -7(x-4)+11=-5x+2(-x-3) | | 2(y+7)-y=10+y-11 | | (7/12)/(3/8) | | 5^2/-3 | | -(4/5)^3 | | 5x-2x+8=2+6x+6 | | 5x-2=-3x+46 | | -(1/2)^2 | | 8-6x=3-5x | | 11*245+16587= | | 4^3/5 | | 5v^2-4=19v | | log(6x-5)=3 | | x^3-7x^2+4x=28 | | 24y^2-12= | | 3(-9+2x)-7x=11x-5 | | 45/9 | | My=Nx | | x^2(x^2-16)-(x^2-16)=0 | | x=3/2*3/2+3/2 | | 5/7=10/x+2 | | 24x-6-18x=2(3x-5)+4 | | 4x-9y=-4 | | 0.25x^2-6x+8=0 | | 9x-11=10+12 | | 6(2t+3)=2(9t+14) | | 0.25x^2-6x+8=y | | 2c^3+8c^2-24c=0 |

Equations solver categories